حقیقة المرض الهولندي في الاقتصادیات الریعیة - bouche, Fatima zohra; khendek, samira (Finance and Business Economies Review, 2017)
The phenomenon of economic Dutch disease is due to the mismanagement of the hydrocarbons sector incomes, at the expense of other sectors, especially the productive ones. This latter entered into recession both in domestic and international markets. This phenomenon has also pushed economies to live in a state of luxury and economic growth, but only in the short term